Long‐term home range stability provides foraging benefits in western gorillas. - Scarry, Clara J.; Salmi, Roberta; Lodwick, Jessica; Doran‐Sheehy, Diane M. (American Journal of Biological Anthropology, 2023)
Objectives: Long‐term home range stability presumably emerges because familiarity with an area improves fitness through increased foraging efficiency, reduced predation risk, or reduced costs of intergroup aggression. While the use of spatial memory by primates has been widely demonstrated, few studies have examined whether long‐term space use creates opportunities for interannual reuse of spatial knowledge. Here we examine the ranging behavior of western gorillas (Gorilla gorilla) to assess the degree of long‐term site fidelity and the foraging consequences of reuse of space. Methods: We measured interannual home range overlap over a 10‐year period for a single group of gorillas at the Mondika Research Center, using both grid‐based and kernel density estimation. By plotting the total area used over time, we identified periods of home‐range stability and expansion. We compared foraging and ranging behavior in familiar versus unfamiliar areas, considering fruit trees visited, dietary diversity, and daily path length, to determine whether the lack of spatial knowledge in unfamiliar areas was associated with foraging costs. Results: Average interannual home range overlap by the group remained high throughout the study. During periods of home range expansion, daily path lengths increased but not the number of fruit trees visited, suggesting that reduced familiarity with the area led to decreased foraging efficiency because individuals lacked prior knowledge of where to find resources. Discussion: Western gorillas at Mondika exhibit long‐term home range stability, presumably reflecting a strategy that relies on the use of spatial memory to increase foraging efficiency that is favored by their reliance on ephemeral fruit resources.